2018
DOI: 10.1094/pdis-05-17-0630-re
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Year Investigation of the Dynamics of Avirulence Allele Profiles, Blackleg Incidence, and Mating Type Alleles ofLeptosphaeria maculansPopulations Associated with Canola Crops in Manitoba, Canada

Abstract: Blackleg, caused by the fungal pathogen Leptosphaeria maculans, is one of the most economically important diseases of canola (Brassica napus, oilseed rape) worldwide. This study assessed incidence of blackleg, the avirulence allele, and mating type distributions of L. maculans isolates collected in commercial canola fields in Manitoba, Canada, from 2010 to 2015. A total of 956 L. maculans isolates were collected from 2010 to 2015 to determine the presence of 12 avirulence alleles using differential canola cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
(71 reference statements)
4
25
0
Order By: Relevance
“…A L. maculans isolate (DS103), termed UMAvr7, was originally identified in a previous study during a canola disease survey in Manitoba, Canada ( Fernando et al, 2018 ). PCR analysis of this isolate, applied to determine the Avr gene profile, indicated that only the AvrLm5 , AvrLm6 , and AvrLm4-7 genes could be positively amplified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A L. maculans isolate (DS103), termed UMAvr7, was originally identified in a previous study during a canola disease survey in Manitoba, Canada ( Fernando et al, 2018 ). PCR analysis of this isolate, applied to determine the Avr gene profile, indicated that only the AvrLm5 , AvrLm6 , and AvrLm4-7 genes could be positively amplified.…”
Section: Resultsmentioning
confidence: 99%
“…A L. maculans isolate (DS103) (hereafter named UMAvr7) collected in a previous study, and carrying the AvrLm5-6-7 gene, was identified ( Fernando et al, 2018 ). The isolate was grown on V8 agar juice medium amended with 0.0035% (w/v) streptomycin sulfate under continuous florescent light at room temperature for one week, before being subjected to a second round of single-pycnidiospore isolation to obtain a pure culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, these have a fairly narrow geographical area coverage. For example, studies into the changes in Avr gene prevalence in the fungal pathogen Leptosphaeria maculans of Brassica crops over time have focussed on single countries such as Canada (Fernando et al, 2018) or Australia (Van de Wouw et al, 2018). On the other hand, studies with a global geographical scope often do not consider the impact of sampling time on changes in Avr factor prevalence.…”
Section: Discussionmentioning
confidence: 99%